Top-Down Synthesis of Nanostructured Platinum-Lanthanide Alloy Oxygen Reduction Reaction Catalysts: Pt xPr/C as an Example - Fichtner, Johannes; Garlyyev, Batyr; Watzele, Sebastian; El-Sayed, Hany A; Schwämmlein, Jan N; Li, Wei-Jin; Maillard, Frédéric M; Dubau, Laetitia; Michalička, Jan; Macak, Jan M; Holleitner, Alexander; Bandarenka, Aliaksandr S (ACS applied materials & interfaces, 2019)
The oxygen reduction reaction (ORR) is of great interest for future sustainable energy conversion and storage, especially concerning fuel cell applications. The preparation of active, affordable, and scalable electrocatalysts and their application in fuel cell engines of hydrogen cars is a prominent step toward the reduction of air pollution, especially in urban areas. Alloying nanostructured Pt with lanthanides is a promising approach to enhance its catalytic ORR activity, whereby the development of a simple synthetic route turned out to be a nontrivial endeavor. Herein, for the first time, we present a successful single-step, scalable top-down synthetic route for Pt-lanthanide alloy nanoparticles, as witnessed by the example of Pr-alloyed Pt nanoparticles. The catalyst was characterized by high-resolution transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, and photoelectron spectroscopy, and its electrocatalytic oxygen reduction activity was investigated using a rotating disk electrode technique. Pt xPr/C showed ∼3.5 times higher [1.96 mA/cm2Pt, 0.9 V vs reversible hydrogen electrode (RHE)] specific activity and ∼1.7 times higher (0.7 A/mgPt, 0.9 V vs RHE) mass activity compared to commercial Pt/C catalysts. On the basis of previous findings and characterization of the Pt xPr/C catalyst, the activity improvement over commercial Pt/C originates from a lattice strain introduced by the alloying process.
Keywords: fuel cell; cathodic corrosion; oxygen reduction; top-down synthesis; platinum alloys; lanthanides; electrocatalysis